Temporal patterns in biodiversity and health status of reef corals of Palk Bay - Sukumaran, Sandhya; George, Rani Mary; Vinod, K.; Sobhana, K. S.; Naomi, T. S.; Manissery, Mary K. (Indian Journal of Fisheries, 2011)
A detailed study aimed at identifying the changes in biodiversity, live coral cover as well as health status of the Palk Bay Reef corals was carried out over a period of 4 years. The live coral percent cover was measured using Line Intercept Transect method at fixed sites in the reefs of Palk Bay in 2008 in order to study and make comparisons with the surveys conducted in 2004. Substantial decrease in live coral cover was observed over the last four years with a live coral cover of 13.65% and 12.9% in Velapertumuni and Kathuvallimuni Reefs respectively. Acropora cytherea and Favites abdita were the dominant and abundant species respectively in Velapertumuni Reef with relative abundance values of 21.08 and 10.85 respectively. However, in Kathuvallimunai Reef, Acropora lamarcki was found to be the most abundant species with a relative abundance value of 12.68. All other species belonged either to common/uncommon species status. Variations in community structure were also noticed in both the reefs. Even though, the total live coral cover was found to be reduced, the increased recruitment of fast growing species like Acropora has contributed to a fair diversity as indicated by the diversity indices. Studies on the disease prevalence in hard corals indicated more incidences of diseases in massive corals as compared to branching corals. Disease conditions such as brown band disease, porites ulcerative white spot syndrome and pink line syndrome/porites pinking were recorded.